Comparative In Vitro Toxicology of Novel Cytoprotective Short-Chain Naphthoquinones - Zikai Feng; Mohammed Sedeeq; Abraham Daniel; Monika Corban; Krystel L. Woolley; Ryan Condie; Iman Azimi; Jason A. Smith; Nuri Gueven (MDPI AG, 2020)
Short-chain quinones (SCQs) have been identified as potential drug candidates against mitochondrial dysfunction, which largely depends on the reversible redox characteristics of the active quinone core. We recently identified 11 naphthoquinone derivatives, 1-11, from a library of SCQs that demonstrated enhanced cytoprotection and improved metabolic stability compared to the clinically used benzoquinone idebenone. Since the toxicity properties of our promising SCQs were unknown, this study developed multiplex methods and generated detailed toxicity profiles from 11 endpoint measurements using the human hepatocarcinoma cell line HepG2. Overall, the toxicity profiles were largely comparable across different assays, with simple standard assays showing increased sensitivity compared to commercial toxicity assays. Within the 11 naphthoquinones tested, the L-phenylalanine derivative 4 consistently demonstrated the lowest toxicity across all assays. The results of this study not only provide useful information about the toxicity features of SCQs but will also enable the progression of the most promising drug candidates towards their clinical use.